2005
DOI: 10.5713/ajas.2006.236
|View full text |Cite
|
Sign up to set email alerts
|

Daidzein Modulations of Apolipoprotein B and Fatty Acid Synthase mRNA Expression in Chick Liver Vary Depending on Dietary Protein Levels

Abstract: This study was designed to determine the effects of daidzein (DE) on hepatic lipid metabolism in chicks fed with low protein (LP) diet based on casein. In experiment 1, the male chicks were fed with one of the three levels of dietary protein containing 10.95%, 21.9% and 43.8% protein content for 2 days. In experiment 2, the chicks were fed one of the three levels of protein with or without DE at 1,000 mg/kg diet for 2 days. Experiment 3 was conducted to compare DE (LP+DE) with estradiol (LP+E2) in chicks fed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…However, Adams and Davis (2001) and Rosebrough et al (2002) found that reducing dietary CP protein content upregulated malic enzyme mRNA expression and elevated the activity of malic enzyme in the liver of broilers compared with the control, whereas increasing dietary CP protein content downregulated malic enzyme mRNA expression and decreased the activity of malic enzyme in the liver of broilers compared with the controls. Choi et al (2006) also showed that increasing dietary protein content caused a significant reduction in FAS mRNA expression in the livers of broiler chickens compared with the controls. Furthermore, Rosebrough et al (2008 ; 2011) found that feeding broilers a diet containing a high CP level suppressed the mRNA expression of hepatic malic enzyme, acetyl coenzyme carboxylase (ACC), and FAS in a comparison of low-protein and high-protein diets.…”
Section: Discusionmentioning
confidence: 85%
“…However, Adams and Davis (2001) and Rosebrough et al (2002) found that reducing dietary CP protein content upregulated malic enzyme mRNA expression and elevated the activity of malic enzyme in the liver of broilers compared with the control, whereas increasing dietary CP protein content downregulated malic enzyme mRNA expression and decreased the activity of malic enzyme in the liver of broilers compared with the controls. Choi et al (2006) also showed that increasing dietary protein content caused a significant reduction in FAS mRNA expression in the livers of broiler chickens compared with the controls. Furthermore, Rosebrough et al (2008 ; 2011) found that feeding broilers a diet containing a high CP level suppressed the mRNA expression of hepatic malic enzyme, acetyl coenzyme carboxylase (ACC), and FAS in a comparison of low-protein and high-protein diets.…”
Section: Discusionmentioning
confidence: 85%
“…이는 낮 은 사료 단백질이 간의 malic enzyme mRNA의 발현 촉진과 malic enzyme의 활성 증가에 의한 결과라고 한다 (Rosebrough et al, 2002). 육계에서 사료 단백질 함량이 높을수록 지방합성 유전자들(malic enzyme, FAS, acetyl coenzyme carboxylase)의 발현이 감소한다 (Choi et al, 2006;Rosebrough et al, 2011). 그러나 위와 같은 단백질 수준에 의한 복부지방의 감소효과는 높은 수준(30% 단백질)의 단백질함 량에 의한 것임을 감안해야 한다.…”
Section: 간의 지방대사 이상unclassified
“…Peningkatan sintesis protein ini tampaknya diperantarai oleh IGF-I dari hepar maupun jaringan lain seperti otot dan ginjal. Lebih lanjut Choi et al (2006) menyatakan bahwa peningkatan kadar protein menyebabkan penurunan yang signifikan terhadap ekspresi mRNA dari enzim FAS (fatty acid synthase) dalam hati ayam. Berkurangnya ekspresi mRNA dari enzim FAS menyebabkan penurunan lipogenesis sehingga menyebabkan berkurangnya deposit lemak abdominal (Fouad dan El-Senousey, 2014).…”
Section: Prosedur Pengujian Kadar Proteinunclassified